Making methamphetamine: Enacting a drug and its consumers in scientific accounts, personal narratives and service provision - Thomson, Nicola Jane (Curtin University, 2014)
This thesis employs post-structuralist and science and technology (STS) theory to critically examine the constitution of methamphetamine and methamphetamine users in scientific, policy, treatment and media texts. Methamphetamine-related practice is also analysed, including how people consume this drug and service provision related to methamphetamine use. The ways in which authoritative discourses shape these practices — how people draw upon, embrace and subvert hegemonic understandings of this drug in their day-to-day lives — are then discussed.